Unnatural flooding alters the functional diversity of riparian vegetation of the Three Gorges Reservoir. (3rd June 2020) - Su, Xiaolei; Bejarano, María Dolores; Yi, Xuemei; Lin, Feng; Ayi, Qiaoli; Zeng, Bo
Abstract: The response of riparian vegetation to flow regulation has been a research focus for decades. Several studies have shed light on the effects of flow stabilisation on riparian woody species, but other life forms exposed to intensified inundation have been overlooked. Furthermore, studies from a functional perspective are scarce. We evaluated the functional response of riparian vegetation along the shores of the Three Gorges Reservoir on the Yangtze River in China to unnaturally long annual flooding (>7 months) after the first year of filling. We aimed to answer the following: (1) can we derive well‐defined flow‐response guilds from the riparian zones of the Yangtze River? and (2) which plant traits and guilds are favoured or disfavoured by the unnaturally long flooding environment? Woody and herbaceous species were inventoried in 12 reaches along the shorelines of the Three Gorges Reservoir and another 12 reaches along the free‐flowing Yangtze River. We performed a cluster analysis to derive riparian guilds using abundance data (projective coverage) from 40 riparian plant species and 13 responsive traits. Structural composition and functional diversity of the unnaturally and naturally flooded riparian vegetation were compared. Unnaturally long flooding substantially reduced species richness, but it did not change the riparian vegetation cover. This novel flooding reduced functional diversity, mostly owing to the loss of stress‐tolerant woody species and competitive perennial herbs. However, competitive annual herbs and flood‐tolerant riparian herbs, as the most abundant functional guilds, were favoured even under such long‐term hypoxic conditions. These guilds under regulation revealed a high functional resilience to prolonged flooding along the upstream reaches of the Yangtze River. Flooding tolerance and the capacity to synchronise germination and growth with short‐exposure periods underlie the plant species changes. Our findings are useful for anticipating the effects of long‐lasting inundation on riparian areas triggered by flow regulation or warmer climates. The functional perspective lends confidence that our conclusions can be generalised to other geographical regions despite not sharing the same species pool. Finally, the plant species that showed a high flooding tolerance should be considered for the restoration of riparian areas affected by the Three Gorges Reservoir.